Biochemical Profiling of the Rinds of Commercial Watermelon Cultivars in Bangalore, Karnataka, India - Safi S.; Vasudeva K. R.; Jagadeesh S. L.; Shivanna M.; Jayashree U; Aravind K. (Archives of Current Research International, 2024)
Watermelon rind, often considered agricultural waste and frequently disposed of, contributes to environmental problems and biomass loss. This study seeks to analyze the distinct Biochemical profiles of watermelon rind, highlighting variations among different cultivars of Bangalore, Karnataka. Total soluble solids, pH, Moisture, titratable acidity, total carbohydrates, total proteins, ash, fat, total energy, fibre, total sugars, total phenolic contents, total antioxidant activity and L*, a*, b* color values were estimated for six local commercial varieties to observe the differences between them. The rinds of all six cultivars had significant variations for all the parameters. This study provides the first-hand knowledge regarding watermelon rind biochemical profiles and cultivar difference and shows the potential use of rind in food or beverages due to its naturally contained bioactive compounds.